Extraction of Cellulosic Compound from Jackfruit Peel Waste and Characterization of PVA Cellulose Composite as Biodegradable Film - Aquib Rahman; Shah Md Ashiquzzaman Nipu; Md Shamsul Alam; S. Sharar Alam; Md. Tanvir Ahmed; Anika Afroz Shantona; Mahjabin Moon (Journal of Engineering)
Plastics utilized in packaging have a significant impact on the environment, leading to considerable concerns regarding human and environmental well-being. Researchers globally are working to counteract these incidents by integrating biopolymers like starch, cellulose, chitosan, etc., into the packaging sector because of their nontoxic nature, biodegradability, and eco-friendly properties. This study aims to extract cellulose from jackfruit (Artocarpus heterophyllus) peel by combining bleaching and alkaline treatment (17.5% w/v NaOH) and utilizes the extracted cellulosic compounds to produce a practical biodegradable film. The constructed film can be an alternative to synthetic films currently used in industries, minimize environmental harm caused by plastics, and offer a waste management option for jackfruit peels. The study extracted 28.04% cellulose from jackfruit peel wastes, and it was subsequently utilized to develop a biocompatible composite film containing polyvinyl alcohol (PVA) and extracted cellulose. The percentage of cellulose being used in PVA is 0%, 20%, 50%, and 80% compared to pure PVA film. Mechanical properties (tensile atrength, elastic modulus, tensile energy absorption, and strain) as well as thermogravimetric analysis (TGA/DTA), Fourier transform infrared (FTIR), water absorption, and soil burial test were done to define the material and functional properties of 0%, 20%, 50%, and 80% cellulose-PVA composite film. Among four films, 20% of the jackfruit-extracted cellulose-reinforced PVA film has shown better results compared to others. It has shown maximum thermal stability at 368.2°C. Conversely, the 50% cellulose-reinforced PVA film has maximum contraction at 57.4°C with a value of 130.6 μm compared to other percentages in terms of thermomechanical analysis. It also shows the maximum water absorption percentage. It is evident from this study that a cellulosic component generated from jackfruit peels can be used with PVA to make biodegradable packaging films.